Management of Thoracic Disc Herniations via Posterior Unilateral Modified Transfacet Pedicle–Sparing Decompression With Segmental Instrumentation and Interbody Fusion. (September 2017) - Carr, Daniel A.; Volkov, Andrey A.; Rhoiney, David L.; Setty, Pradeep; Barrett, Ryan J.; Claybrooks, Roderick; Bono, Peter L.; Tong, Doris; Soo, Teck M.
Study Design: Retrospective consecutive case series. Objective: The objective of this case series was to demonstrate the safety of a modified transfacet pedicle–sparing decompression and instrumented fusion in patients with thoracic disc herniations (TDHs). Methods: Consecutive patients undergoing operative management of TDH from July 2007 to December 2011 using a posterior unilateral modified transfacet pedicle–sparing approach were identified. All patients underwent open or minimally invasive modified transfacet pedicle–sparing discectomy and segmental instrumentation with interbody fusion, performed by four different surgeons. Pre- and postoperative visual analog scale (VAS) pain scores, Nurick grade, and American Spinal Injury Association Impairment Scale (AIS) were analyzed from a retrospective chart review. Estimated blood loss and complications were also obtained. Results: Fifty-one patients were included that had operations for TDH. Thirty-nine patients had single level decompression and 12 had multilevel decompression. The total number of levels operated on was 64. Five patients were treated with minimally invasive surgery. A herniated disc level of T11-12 (n = 17) was treated most often. One major complication of epidural hematoma occurred. Minor complications such as malpositioned hardware, postoperative hematoma, wound infection, pseudoarthrosis, and pulmonary complications occurred in a few patients. Follow-up ranged from 1 to 46 months with 1 patient lost to follow-up. From preoperative to final postoperative: mean VAS scores improved from 8.31 to 4.05, AIS in all patients remained stable or improved, and Nurick scores improved from 3 to 2.6 on average. No intraoperative or permanent neurological deficit occurred. Conclusion: In our surgical series, 51 consecutive patients underwent modified transfacet pedicle–sparing approach to TDHs and experienced improvement of functional status as well as improvement of objective pain scales with no neurological complications. The posterior unilateral modified transfacet pedicle–sparing decompression and instrumented fusion approach to the thoracic spine is a safe and reproducible procedure for the treatment of TDHs.